EFFECT OF E-GOVERNMENT AND INTERNAL CONTROL SYSTEM ON PERFORMANCE ACCOUNTABILITY - Rossa Amalia Rizky; Syntha Noviyana (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The study of the factors that affect the accountability of the performance of government agencies is still an important issue in determining strategies to achieve the vision, mission, goals, and objectives. This study aims to develop a previous empirical research model regarding implementing e-government, internal control systems on performance accountability. Research data was obtained from the questionnaire answers to 50 Civil Servants working at the Transportation Agency City of Pekanbaru. The sample was selected with the criteria set by the purposive sampling method, and the data were analyzed by multiple linear regression. Data processing uses SPSS version 25. The results show that the implementation of e-government and internal control systems partially and simultaneously affects the accountability of the performance of the Transportation Agency City of Pekanbaru.